1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Differential Equation

  1. Mar 31, 2008 #1
    dy/dx = (3x^2)(e^-y)

    1/(e^-y) dy = 3x^2 dx
    1/(e^-y) = x^3 + C

    Can anybody please give me any help or advice on to where to go from here? I'm having a really tough time with this one.
  2. jcsd
  3. Mar 31, 2008 #2

    this diff. eq. can be solved with separation of variables.So:

    [tex]e^{y}dy=3x^{2}dx[/tex] now integrate both sides and solve for y.
  4. Mar 31, 2008 #3
    So, y = ln(x^3+C)?
  5. Mar 31, 2008 #4
    Looks like it is right.
  6. Mar 31, 2008 #5
    Thanks stupidmath!!! Now, if I wanted to solve, for example y(0)=1

    ln (C) = y - ln(x^3)
    ln (C) = 1 - 0
    C = e^1 ?

    y = ln(x^3) + e^1 ?
  7. Mar 31, 2008 #6
    Well, to impose the initial condition y(0)=1, you actually here have that when x=0, y=1.

    So it means:


    so our particular solution would be


    You just misplaced the parentheses on your final answer.
  8. Mar 31, 2008 #7
    Ah, thanks a bunch stupidmath!!!
  9. Mar 31, 2008 #8
    One last question stupidmath. wouldn't dy/dx = 4(2y-1) end up being y = Ce^-32x?
  10. Apr 1, 2008 #9


    User Avatar
    Science Advisor

    It is not "stupidmath". Beware of his ire!

    You should be able to do this one yourself now. If dy/dx= 4(2y-1) then dy/(2y-1)= 4dx.
    Integrating on both sides (1/2)ln|2y-1|= 4x+ C so ln|2y-1|= 8x+ C' (C'= 2C). Then 2y-1= C"e^(8c).
  11. Apr 1, 2008 #10


    User Avatar
    Science Advisor
    Homework Helper
    Gold Member
    Dearly Missed

    It is suttypud-math, not stupidmath!
  12. Apr 1, 2008 #11
    Oh, I apologize for the faux pas sutupidmath. I also appreciate the help, thanks.
  13. Apr 1, 2008 #12
    Is there any meaning to this?:smile:
  14. Apr 2, 2008 #13


    User Avatar
    Homework Helper

    Remember that ln(a + b) =/= ln(a) + ln(b), which is what you did here.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook